Examining text complexity in the early grades. (May 2016) - Fitzgerald, Jill; Elmore, Jeff; Hiebert, Elfrieda H.; Koons, Heather H.; Bowen, Kimberly; Sanford-Moore, Eleanor E.; Stenner, A. Jackson
The Common Core raises the stature of texts to new heights, creating a hubbub. The fuss is especially messy at the early grades, where children are expected to read more complex texts than in the past. But early-grades teachers have been given little actionable guidance about text complexity. The authors recently examined early-grades texts to discover what makes them complex and now report that there is a lot that can help teachers, specifically, young children's texts are special, a handful of text characteristics can signal text-complexity level, sometimes the interplay of text characteristics modulates text-complexity level, and knowing why a text is complex can facilitate text selection.